Statistical Modeling of Lower Limb Kinetics During Deep Squat and Forward Lunge - De Roeck, Joris; Van Houcke, J.; Almeida, D.; Galibarov, P.; De Roeck, L.; Audenaert, Emmanuel A. (Frontiers in Bioengineering and Biotechnology, 2020)
Purpose – Modern statistics and higher computational power have opened novel possibilities to complex data analysis. While gait has been the outmost described motion in quantitative human motion analysis, descriptions of more challenging movements like the squat or lunge are currently lacking in the literature. The hip and knee joints are exposed to high forces and cause high morbidity and costs. Pre-surgical kinetic data acquisition on a patient-specific anatomy is also scarce in the literature. Studying the normal inter-patient kinetic variability may lead to other comparing studies to initiate more personalized therapies within the orthopedics. Methods – Trials are performed by 53 healthy young males without overweight and approximately the same age and activity level. Spatial marker trajectories and ground reaction force registrations are imported into in the Anybody Modeling System, based on subject-specific geometry and the state-of-the-art TLEM 2.0 dataset. Hip and knee joint reaction forces were obtained by a simulation with an inverse dynamics approach. With these forces, a statistical model that accounts for inter-subject variability was created. For this, we applied a principal component analysis in order to enable variance decomposition. This way, noise can be rejected and we still contemplate all waveform data, instead of using deduced spatiotemporal parameters like peak flexion or stride length, as done in many gait analyses. In addition, this current paper is, to the authors’ knowledge, the first to investigate generalization of a kinetic model data towards the population. Results – Average knee reaction forces range up to 7.16 times body weight for the forwarded leg during lunge. Conversely, during squat is the load evenly distributed. For both motions, a reliable and compact statistical model was created. In the lunge model, the first 12 modes accounts for 95.26% of inter-individual population variance. For the maximal-depth squat, this was 95.69% for the first 14 modes. Model accuracies will increase when including more principal components. Conclusion – Our model design was proved to be compact, accurate and reliable. For models aimed at population covering descriptive studies, the sample size must be at least 50.